2016
DOI: 10.1002/ar.23314
|View full text |Cite
|
Sign up to set email alerts
|

The Digestive Tract and Derived Primordia Differentiate by Following a Precise Timeline in Human Embryos Between Carnegie Stages 11 and 13

Abstract: The precise mechanisms through which the digestive tract develops during the somite stage remain undefined. In this study, we examined the morphology and precise timeline of differentiation of digestive tract-derived primordia in human somite-stage embryos. We selected 37 human embryos at Carnegie Stage (CS) 11-CS13 (28-33 days after fertilization) and threedimensionally analyzed the morphology and positioning of the digestive tract and derived primordia in all samples, using images reconstructed from histolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Such morphometric data are useful for demonstrating the development features at each stage as well as for screening abnormally developed samples. We can select abnormal samples adequately in the liver and digestive tract (Kanahashi et al, ; Ueno et al, ) (Figs. and ; Video 2: https://players.brightcove.net/656326989001/default_default/index.html?videoId=5729925007001; Video 3: https://players.brightcove.net/656326989001/default_default/index.html?videoId=5729925073001).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Such morphometric data are useful for demonstrating the development features at each stage as well as for screening abnormally developed samples. We can select abnormal samples adequately in the liver and digestive tract (Kanahashi et al, ; Ueno et al, ) (Figs. and ; Video 2: https://players.brightcove.net/656326989001/default_default/index.html?videoId=5729925007001; Video 3: https://players.brightcove.net/656326989001/default_default/index.html?videoId=5729925073001).…”
Section: Resultsmentioning
confidence: 99%
“… 3D reconstructions of the digestive tract and derived primordia in CS13 from ( A ) normal and ( B ) abnormal embryos. We created a precise timeline of events for the development and differentiation of the digestive tract and derived primordia between CS11 and CS13 (Ueno et al, ). (a) Embryo in which the events of differentiation matched the timeline.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Blechschmidt Collection has not been subjected to a digitization project thus far. In 2014, some of the present authors from Kyoto University scanned sections in Göttingen and found the specimens to be in suitable condition for research (Ueno et al 2016). On this basis, the decision was made to scan the remaining slides of the Blechschmidt Collection, and the digitization of the collection commenced in 2015.…”
Section: Introductionmentioning
confidence: 99%